Implementation Of Regulation And Spatial / Head Of National Land Agency Number 2 Of 2018 On Development And Supervision Of The Land Deed Official (PPAT) - Siti Rohaeti; Jawade hafidz (Jurnal Akta, 2019)
The purpose of this study was to describe the shape and scope of the Development and Supervision PPAT and for Knowing Function and Purpose Implementation and Monitoring of the PPAT developing and to know the effects in Implementation of Development and Supervision of the Land Deed Official (PPAT) Semarang.This study uses the Juridical Sociological Approach. The method used is Qualitative Research Methods in the form of observations, interviews, or review of documents.The form and scope of guidance and supervision over the PPAT in Semarang done by conducting seminars, debriefing and sharing the latest information in the world of PPAT or the development of new regulations and land surrounding PPAT. Direct guidance in the sense of providing direction directly linked PPAT, Application function of supervision by the Land Deed Official Officials at the Land Office of Semarang walk quite optimal in accordance with the legislation in force, hanya only in terms of the emergence of new regulations concerning the Council of Trustees and the Supervisory Officer of the Land Deed at the central level, region and area is still in the formation process and the preparation of Inhibiting factors in the application function of supervision by the Land Deed Official Officials at the Land Office of Semarang. The ratio between the number of PPAT by the number of clerks Land Office Land Office allows limited ability to be able to perform to the maximum guidance and supervision of the PPAT in Semarang.Keywords: Guidance; Control; Land Deed Official (PPAT)